2020
DOI: 10.36740/wlek202010104
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Limits the Progression of Oxidative and Nitrosative Stress in the Rats’ Tissues After Experimental Traumatic Brain Injury

Abstract: The aim: To investigate the effect of water-soluble form of quercetin on the indices reflecting the progression of oxidative-nitrosative stress in the cerebral tissues and the periodontium of rats after experimental TBI. Materials and methods: The studies were conducted on 30 white rats of the Wistar line weighing 180-220 g, divided into 3 groups: the 1st group included pseudo-injured animals (subjected to ether anaesthesia, fixation without TBI modeling), the 2nd group included the animals exposed to modeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…It is evident that under these conditions the normalisation of the melatonin level is not sufficient to correct metabolic disorder, which can be achieved by suppressing the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) or by inducing the nuclear-factor-E2-related factor-2 (Nrf2), antagonistic to NF-κB [ 9 , 10 ]. The best safety profile among agents that can inhibit NF-κB and/or activate Nrf2 is found in plant polyphenols, particularly in bioflavonoids, epigallocatechin-3-gallate [ 11 , 12 ], and quercetin [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that under these conditions the normalisation of the melatonin level is not sufficient to correct metabolic disorder, which can be achieved by suppressing the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) or by inducing the nuclear-factor-E2-related factor-2 (Nrf2), antagonistic to NF-κB [ 9 , 10 ]. The best safety profile among agents that can inhibit NF-κB and/or activate Nrf2 is found in plant polyphenols, particularly in bioflavonoids, epigallocatechin-3-gallate [ 11 , 12 ], and quercetin [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The syndrome of endogenous intoxication is accompanied by increased tissue breakdown, increased catabolic processes due to the accumulation of excessive amounts of biologically active substances, deformed protein metabolites and other toxic substances of endogenous origin (Yavtushenko et al 2020). The increase in the level of erotric acid intoxication index is explained by the toxic effect on erythrocyte membranes, which was manifested by a significant increase on the 14 th day of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic study demonstrated that quercetin promoted the translocation of Nrf2 from the cytoplasm to the nucleus, suggesting that quercetin exerts neuroprotective effects in TBI mice via maintaining mitochondrial homeostasis through the activation of Nrf2 signaling pathway [ 76 ]. In moderate TBI rats, quercetin inhibited oxidative nitrosative stress by reducing the activity of NOS including inducible nitric oxide synthase (iNOS) and constructive nitric oxide synthase (cNOS), as well as the concentration of thiobarbituric acid (TBA)-lipid peroxidation in the cerebral hemisphere and periodontal tissues [ 77 ]. Therefore, quercetin exerts neuroprotective effects in TBI via multiple biological activities, including inhibition of oxidative damage, nitrosative stress, and inflammatory response, as well as the improvement of mitochondrial dysfunction and neuronal function through the Nrf2 signaling pathway.…”
Section: The Potential Therapy Of Phytochemicals As Nrf2 Activators I...mentioning
confidence: 99%